2016
DOI: 10.21608/jppp.2016.50085
|View full text |Cite
|
Sign up to set email alerts
|

ULTRA STRUCTURAL DELETERIOUS IN THE COTTON LEAF WORM, Spodoptera littoralis (BOISD.) LARVAE TREATED WITH CERTAIN INSECTICIDES

Abstract: Cypermethrin, esfenvalerate, chlorpyrifos and Bacillus thuringiensis, Kurs. were tested against the cotton leaf worm, Spodoptera littoralis (Boisd.) treated as 4 th instar larvae. In addition, LC 50 , s of tested compounds were applied on S. littoralis larvae to investigate the ultra structural changes in the integument, muscle, fat body and mid gut of alive and dead larvae. Meanwhile, the nerve cord sections were investigated for alive larvae only. All investigations were done by light and electronic microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition to the mode of action, the profenofos compound on acetyle cholinesterase in insect; Osman and Abou-Zaid (2015) found that destruction of some cells in midgut and cuticle layers of S. littoralis that treated with profenofos. Hassan, et al (2016) found the toxicity and ultrastructural studies cleared that tested compound of cypermethrin, esfenvalerate, chlorpyrifos and B. thuringiensis had destroyed influence on alive and dead S. littoralis larvae in integument, muscle, fat body and midgut when the larvae treated as fourth instar larvae as compared with control. Meanwhile, chlorpyrifos was the most neurotoxicity agent than other tested compounds.…”
Section: B Lint Weight (G)mentioning
confidence: 88%
“…In addition to the mode of action, the profenofos compound on acetyle cholinesterase in insect; Osman and Abou-Zaid (2015) found that destruction of some cells in midgut and cuticle layers of S. littoralis that treated with profenofos. Hassan, et al (2016) found the toxicity and ultrastructural studies cleared that tested compound of cypermethrin, esfenvalerate, chlorpyrifos and B. thuringiensis had destroyed influence on alive and dead S. littoralis larvae in integument, muscle, fat body and midgut when the larvae treated as fourth instar larvae as compared with control. Meanwhile, chlorpyrifos was the most neurotoxicity agent than other tested compounds.…”
Section: B Lint Weight (G)mentioning
confidence: 88%